Integrated Methylome and Transcriptome Analysis between the CMS-D2 Line ZBA and Its Maintainer Line ZB in Upland Cotton - Zhang, Meng (Int J Mol Sci, 2019)
DNA methylation is an important epigenetic modification involved in multiple biological processes. Altered methylation patterns have been reported to be associated with male sterility in some plants, but their role in cotton cytoplasmic male sterility (CMS) remains unclear. Here, integrated methylome and transcriptome analyses were conducted between the CMS-D2 line ZBA and its near-isogenic maintainer line ZB in upland cotton. More methylated cytosine sites (mCs) and higher methylation levels (MLs) were found among the three sequence contexts in ZB compared to ZBA. A total of 4568 differentially methylated regions (DMRs) and 2096 differentially methylated genes (DMGs) were identified. Among the differentially expressed genes (DEGs) associated with DMRs (DMEGs), 396 genes were upregulated and 281 genes were downregulated. A bioinformatics analysis of these DMEGs showed that hyper-DEGs were significantly enriched in the “oxidative phosphorylation” pathway. Further qRT-PCR validation indicated that these hypermethylated genes (encoding the subunits of mitochondrial electron transport chain (ETC) complexes I and V) were all significantly upregulated in ZB. Our biochemical data revealed a higher extent of H(2)O(2) production but a lower level of adenosine triphosphate (ATP) synthesis in CMS-D2 line ZBA. On the basis of the above results, we propose that disrupted DNA methylation in ZBA may disrupt the homeostasis of reactive oxygen species (ROS) production and ATP synthesis in mitochondria, triggering a burst of ROS that is transferred to the nucleus to initiate programmed cell death (PCD) prematurely, ultimately leading to microspore abortion. This study illustrates the important role of DNA methylation in cotton CMS.